1992
DOI: 10.1164/ajrccm/146.6.1402
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Repetitive Airway Obstruction on O2Saturation and Systemic and Pulmonary Arterial Pressure in Anesthetized Dogs

Abstract: We examined the effects of multiple repetitive airway obstruction (RAO) on arterial oxygen saturation (SaO2) and pulmonary and systemic arterial pressure in eight anesthetized spontaneously breathing dogs. SaO2 was monitored at the tongue with a pulse oximeter. RAO created by an electrical valve that was attached to a tracheal cannula was alternated with seven consecutive spontaneous breaths until the nadir SaO2 (nSaO2) became constant or decreased to less than 35%. Tracheal occlusion durations of 15, 30, 45 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
23
1
3

Year Published

1994
1994
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 6 publications
2
23
1
3
Order By: Relevance
“…On the other hand, increasing Pa,CO 2 by 1.4 kPa in anaesthetised dogs increased arterial pressure only by about 5 mmHg [13] when blood pressure increased more than 20 mmHg during the obstructive period in sleep apnoea [1]. These results [3,5,7] conflict with previous data [1,[8][9][10] and our finding showing the predominant role of hypoxaemia over hypercapnia in acute changes in SBP, DBP and HR. In our study, increases in SBP were higher with HOHC (+35.1±26.4 mmHg) than with HO (+25.3±25.7 mmHg) and HR decreased more with HOHC, (severe, -139.3±75.7 bpm; mild, -28.5±52.0 bpm) than HO (severe, -93.8±124.1 bpm; mild, -3.1±67.8 bpm) ( fig.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…On the other hand, increasing Pa,CO 2 by 1.4 kPa in anaesthetised dogs increased arterial pressure only by about 5 mmHg [13] when blood pressure increased more than 20 mmHg during the obstructive period in sleep apnoea [1]. These results [3,5,7] conflict with previous data [1,[8][9][10] and our finding showing the predominant role of hypoxaemia over hypercapnia in acute changes in SBP, DBP and HR. In our study, increases in SBP were higher with HOHC (+35.1±26.4 mmHg) than with HO (+25.3±25.7 mmHg) and HR decreased more with HOHC, (severe, -139.3±75.7 bpm; mild, -28.5±52.0 bpm) than HO (severe, -93.8±124.1 bpm; mild, -3.1±67.8 bpm) ( fig.…”
Section: Discussioncontrasting
confidence: 88%
“…In agreement with this finding, STOOHS and GUILLEMINAULT [8] demonstrated in five men with severe obstructive sleep apnoea, that mean blood pressure always increased during the obstructive period and that the changes in HR were correlated with the degree of hypoxaemia. In experimental models of repetitive airway obstruction in anaesthetised dogs, IWASE et al [9] showed that the main factor in the increase in systemic arterial pressure during repetitive airway obstruction was hypoxaemia and that hypercapnia and acidosis had no significant effects. Increases in apnoeic and postapnoeic blood pressure correlate with the degree of hypoxia during apnoea [1].…”
Section: Discussionmentioning
confidence: 99%
“…The factors which have been proposed for the pathogenesis of Ppa changes in OSA are: changes in cardiac output [3,5], the mechanical influences of intrathoracic pressure swings [6,7], and hypoxia [1,4,5,8].…”
mentioning
confidence: 99%
“…In fact, Ppa during sleep increases more during room air breathing than during oxygen administration [5]; Ppa values during OSA are usually inversely correlated with arterial oxygen tension (PaO 2 ) or oxyhaemoglobin saturation (SaO 2 ) values [1,4]; and Ppa at apnoea termination increases as SaO 2 decreases during repetitive airway occlusion trials in dogs [8]. However, when oxygen was administered to blunt SaO 2 oscillations during OSA occurring in non rapid eye movement sleep (NREM) sleep, no significant effect was found on transmural Ppa oscillations within apnoeas [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation